1990
DOI: 10.1523/jneurosci.10-04-01268.1990
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor-dependence of herpes simplex virus latency in peripheral sympathetic and sensory neurons in vitro

Abstract: Previously, we reported that nerve growth factor (NGF) is required to maintain herpes simplex virus (HSV) latency in cultures of rat sympathetic neurons (Wilcox and Johnson, 1987, 1988). Here, we extend these results by showing that NGF was also required to maintain HSV latency in cultures of sensory neurons obtained from dorsal root ganglia of rats, monkeys, and humans. The interruption of the neuronal supply of NGF for 1 hr reactivated HSV, indicating that the latent virus was exquisitely sensitive to pertur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
139
1
3

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(150 citation statements)
references
References 39 publications
5
139
1
3
Order By: Relevance
“…Reactivation from latency almost certainly occurs in the absence of VP16 and therefore cellular controls are thought to be crucial in this context (O'Rourke & O'Hare, 1993 ;Ralph et al, 1994). It has been shown that HSV-1 is reactivated from latency in cultured foetal rat neurons by transient treatment with cycloheximide (Wilcox et al, 1990) and the results presented here suggest that this effect is a consequence of activating HSV-1 IE promoters. In addition, a recent study speculates that stimulation of cellular IE gene expression may be an important prerequisite for reactivation of HSV-1 after explant of latently infected neurons (Tal-Singer et al, 1997).…”
Section: Discussionsupporting
confidence: 57%
“…Reactivation from latency almost certainly occurs in the absence of VP16 and therefore cellular controls are thought to be crucial in this context (O'Rourke & O'Hare, 1993 ;Ralph et al, 1994). It has been shown that HSV-1 is reactivated from latency in cultured foetal rat neurons by transient treatment with cycloheximide (Wilcox et al, 1990) and the results presented here suggest that this effect is a consequence of activating HSV-1 IE promoters. In addition, a recent study speculates that stimulation of cellular IE gene expression may be an important prerequisite for reactivation of HSV-1 after explant of latently infected neurons (Tal-Singer et al, 1997).…”
Section: Discussionsupporting
confidence: 57%
“…The systems with the most obvious relevance to latency in animals and humans utilize foetal neurons from rats or primates (Wigdahl et al, 1983(Wigdahl et al, , 1984bWilcox & Johnson, 1987Wilcox et al, 1990). Infection of cultured rat foetal neurons with HSV is non-productive provided an inhibitor of DNA synthesis is present for a few days after infection and nerve growth factor (NGF) is included in the culture medium.…”
Section: Introductionmentioning
confidence: 99%
“…Infection of cultured rat foetal neurons with HSV is non-productive provided an inhibitor of DNA synthesis is present for a few days after infection and nerve growth factor (NGF) is included in the culture medium. Removal of NGF, or addition of agents that antagonize its effect, results in reactivation of latent HSV (Wilcox & Johnson, 1987Wilcox et al, 1990). Despite its obvious attractions, extensive use of this system is hindered by the limited quantity of neurons that can readily be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…In effect, excised ganglia bathed in nutrient medium resemble in substance the severed human ganglion left to atrophy and reactivate virus. The modification we introduced in this model is based on the observation reported by Wilcox et al (13,14) and Camarena et al (15) that nerve growth factor (NGF) blocks virus replication in explanted neurons in vitro. Because a key requirement of our model is to accelerate reactivation and compress the interval of maintenance of explanted ganglia, we tested the effects of both NGF and anti-NGF antibody on viral gene expression.…”
mentioning
confidence: 99%